Physical Condition Profile of Female Futsal Athletes at Childroom FC Bangkalan - Rusdiana, Ariska; Himawan, Agus; Hidayatullah, Fajar; Purwoto, Septyaningrum Putri (Journal of Sport and Exercise Science, 2024)
Purpose: Physical characteristics are the basic things needed for futsal athletes who want to achieve high achievements. This research aims to understand and describe the real situation regarding the physical condition of 15 21 year old Childroom FC Bangkalan futsal athletes. Materials and Methods: This research method is quantitative through surveys. There are six types of physical tests carried out at the Childroom FC Bangkalan women's futsal club, such as push up tests to measure arm and shoulder muscle strength, sit up evaluations used to assess strength in the abdominal muscles, 10 meter sprints carried out to measure speed levels, evaluations Illinois run and agility are used to evaluate the level of agility and coordination, standing long jumps are used to measure strength in the leg muscles, and the level 2 intermittent yo-yo test is used to assess heart and lung endurance. The respondents in this study were 15 athletes under the age of 21 from the Childroom FC Bangkalan women's futsal club. This research was conducted at the Dwi Champion Jengkebuen Bangkalan futsal field. Result: The average results from the test were push ups 34.6, sit ups 30.6, 10 meter sprint 2.95, Illinois run and agility test 21.57, standing long jump 6.9, and yoyo intermittent level 2 3.79. Conclusion: From this research, the test results showed a large effect physical training at the Childroom FC Bangkalan women's futsal club.